2021
DOI: 10.1101/2021.12.23.474002
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurons burdened by DNA double strand breaks incite microglia activation through antiviral-like signaling in neurodegeneration

Abstract: DNA double strand breaks (DSBs) are linked to aging, neurodegeneration, and senescence. However, the role played by neurons burdened with DSBs in disease-associated neuroinflammation is not well understood. Here, we isolate neurons harboring DSBs from the CK-p25 mouse model of neurodegeneration through fluorescence-activated nuclei sorting (FANS), and characterize their transcriptomes using single-nucleus, bulk, and spatial sequencing techniques. We find that neurons harboring DSBs enter a late-stage DNA damag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…Knockdown of Rel in Drosophila neurons promotes survival (Kounatidis et al, 2017), whereas activation of the Rel signaling pathway leads to neurodegeneration (Cao et al, 2013). Consistent with our results, a recent re-analysis of snRNAseq data from Mathys et al (2019) revealed AD-associated perturbation of NFκB immune pathways in excitatory neurons, possibly triggered by DNA double strand breaks (Welch et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Knockdown of Rel in Drosophila neurons promotes survival (Kounatidis et al, 2017), whereas activation of the Rel signaling pathway leads to neurodegeneration (Cao et al, 2013). Consistent with our results, a recent re-analysis of snRNAseq data from Mathys et al (2019) revealed AD-associated perturbation of NFκB immune pathways in excitatory neurons, possibly triggered by DNA double strand breaks (Welch et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…Overall, our results suggest that besides the well-established requirements in glia (see below), innate immune response pathways may also have important, cell autonomous roles in modulating neuronal vulnerability to tau pathology in AD. Indeed, both insect and mammalian neurons express evolutionary-conserved innate immune signaling pathways, including Toll-like receptors and NFκB signal transduction components, and these pathways can be triggered by infection or other cellular insults (Lehnardt et al, 2003;Tang et al, 2007;Cao et al, 2013;Cho et al, 2013;Welch et al, 2022). In addition, NFκB immune signaling pathways have been coopted for diverse, non-canonical functions, such as in neurodevelopment and synaptic plasticity (Okun et al, 2011;Gutierrez and Davies, 2011;Nguyen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Genome instability with increased DNA double strand breaks (DSBs) is detrimental to neurons of the brain and has been implicated in diverse neurodegenerative disorders (NDs) [1][2][3][4][5][6] . However, the etiology of NDs is multifaceted, the progressive decline in number and activity of neurons exhibits significant comorbidity with glial and cerebrovascular abnormalities [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%